An investigation of cracks caused by concrete shrinkage and temperature difference in common reinforced concrete bridge structures. (Fracture and Structural Integrity, 2024)
This research investigates cracking in Reinforced Concrete Structures (RCS), particularly in bridge abutments, box girders, and culverts. Cracks often appear even after the concrete has reached its full strength. The current American Bridge Design Standard (AASHTO) permits cracks but doesn’t specify quantitative limits on crack widths. This study uses the fib MODEL CODE 2010 (fib) to analyze RCS under shrinkage and temperature loading. It was found that cracks often exceed fib’s allowable limits, primarily due to significant temperature differences between concrete and steel reinforcement. This is especially prevalent in larger structures with high hydration heat. The use of smaller diameter reinforcement can significantly reduce crack width compared to larger ones, given the same steel ratio. However, a high steel ratio, while reducing crack width, increases susceptibility to cracking. Cracks typically occur after several weeks to months, with widths ranging from 0.30 to 0.70 millimeters due to shrinkage and temperature differences. These findings underscore the importance of considering both shrinkage and temperature differences in the design and maintenance of RCS. By understanding the impact of these factors, as well as the role of reinforcement diameter and steel ratio, engineers can develop more effective strategies for managing and mitigating cracking.
Keywords: Crack in reinforced concrete; Concrete bridges; Tension chord model; Crack width; Concrete shrinkage and temperature differences; Crack control